The covariation of South African and foreign equity returns during bull and bear runs : implications for portfolio diversification - Mhlanga, Godfrey (Rhodes University, Faculty of Commerce, Department of Economics, 2009)
This study examines the pattern of covariation of the industrial index returns of South Africa and foreign industrial sectors. This follows recent increase in national equity correlations and increases in the influence of industry effects in portfolio diversification. The covariation pattern in returns across industries and countries during both bull and bear runs is examined using correlation analysis to determine if there is a difference between the two epochs. The study presents preliminary evidence of the covariation between sectors during a bear and a bull run. Return covariation among sectors is impelled to a greater extent by country-specific factors than by industry-specific factors, implying the segmentation of industrial sectors. Thus, South African investors can in general gain more if a portfolio comprising shares across industries and countries is held, even if these investors buy shares from similar industries.
Keywords: Stock exchanges -- South Africa; Portfolio management -- South Africa; Investments -- South Africa